Study on the Corrosion Resistance of Thermal Spraying Zinc AluminumCoating with High Aluminum Content - ZHANG Yong-fa, GAO Ming-chuan, CHEN Tong-zhou, PAN Lin, WU Mian (Cailiao Baohu, 2021)
In order to explore the corrosion resistance of zinc-aluminum coatings with high aluminum content, the thermal spraying technology was applied to produce three kinds of high-aluminum zinc-aluminum coatings. The corrosion resistance of zinc aluminum coatings with different aluminum contents were investigated by ultra-depth filed microscope, electrochemical polarization curves, electrochemical impedance spectroscopy (EIS) and X-ray diffractometer(XRD). Results showed that the Zn-containing coating first underwent the activation and dissolution of zinc during the corrosion process, and the corrosion products attached to the coating surface induced that the coating exhibited a weak self-sealing effect. Furthermore, owing to holding the cathodic protection of zinc and the passivation shielding effect of aluminum, the Zn-Al60 coating presented the optimal corrosion resistance among the three kinds of coatings.